2016
DOI: 10.1523/jneurosci.1376-14.2016
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles of Direct and Indirect Frontoparietal Pathways for Individual Working Memory Capacity

Abstract: The ability to temporarily store and manipulate information in working memory is a hallmark of human intelligence and differs considerably across individuals, but the structural brain correlates underlying these differences in working memory capacity (WMC) are only poorly understood. In two separate studies, diffusion MRI data and WMC scores were collected for 70 and 109 healthy individuals. Using a combination of probabilistic tractography and network analysis of the white matter tracts, we examined whether s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 63 publications
5
41
0
4
Order By: Relevance
“…We also recorded task-related behavior, driving behavior, and peripheral physiology to simultaneously assess working memory load with measures other than fNIRS recordings. Our hypothesis is that neural activation patterns in the pre-frontal and parietal areas will be the relevant features for estimating the level of working memory load since previous laboratory studies have shown that these areas are known to be involved in working memory-related processing (LaBar et al, 1999; Wagner et al, 2005; Postle, 2006; Koenigs et al, 2009; Salazar et al, 2012; Lara and Wallis, 2015; Ekman et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…We also recorded task-related behavior, driving behavior, and peripheral physiology to simultaneously assess working memory load with measures other than fNIRS recordings. Our hypothesis is that neural activation patterns in the pre-frontal and parietal areas will be the relevant features for estimating the level of working memory load since previous laboratory studies have shown that these areas are known to be involved in working memory-related processing (LaBar et al, 1999; Wagner et al, 2005; Postle, 2006; Koenigs et al, 2009; Salazar et al, 2012; Lara and Wallis, 2015; Ekman et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Preserved connectivity within this circuit in the PD group contrasted with left middle frontal (BA 6)—right inferior parietal cortex connectivity, which was upregulated during distraction. Thus, opposite frontoparietal connectivity patterns were observed in homologous circuits that are pivotal for WM, which is compatible with compensation in PD when the demands on focused spatial attention are amplified (Ekman et al, ). Likewise, in both groups right putamen and bilateral precuneus couplings were stronger in the absence of distraction, possibly reflecting preserved updating (McNab & Klingberg, ) and storage (Galeano Weber et al, ) in PD when focusing attention is easier.…”
Section: Discussionmentioning
confidence: 87%
“…This loss in connectivity resembled PD patients' loss in coupling of a similar circuit (left putamen—BA 8) when encoding during distraction. Both findings suggest that frontostriatal dysfunction disrupts flexible updating of WM (Ekman et al, ; Hazy et al, ; McNab & Klingberg, ). Although load‐related putamen coupling in the control group was found with more distributed prefrontal regions (BA 8, DLPFC), this finding may reflect the higher demands of updating four relevant shapes in comparison to arrays of the same size that contain two relevant items and two distractors (Badre & Nee, ; Linden et al, ; Nee & Brown, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations